2021
DOI: 10.1002/ppul.25287
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin‐D supplementation as an adjunct to standard treatment of asthma in children: A randomized controlled trial (ViDASTA Trial)

Abstract: Objective: To determine the role of vitamin D supplementation as an adjunct to standard treatment in childhood asthma.Study Design: In this placebo-controlled, blinded, randomized controlled trial, we enrolled 60 children aged 6 to 11 years with moderate persistent asthma and randomly assigned them into intervention (2000 IU per day of vitamin D) and placebo groups (n = 30 each). The primary outcome was asthma control as assessed by the childhood asthma control test (C-ACT) scores at 12 weeks post-randomizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 23 publications
1
38
0
2
Order By: Relevance
“…The primary outcome data are presented in figure 2 . Nine trials reported data on corticosteroid use [ 9 , 15 , 16 , 21 , 25 , 26 , 31 , 32 , 36 ]. Seven trials (654 participants) compared the requirement of rescue systemic steroids in an asthma attack [ 14 16 , 21 , 25 , 26 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome data are presented in figure 2 . Nine trials reported data on corticosteroid use [ 9 , 15 , 16 , 21 , 25 , 26 , 31 , 32 , 36 ]. Seven trials (654 participants) compared the requirement of rescue systemic steroids in an asthma attack [ 14 16 , 21 , 25 , 26 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full texts of these studies, eight RCTs involving 738 children (376 children took vitamin D and 362 took placebos) were included in our meta-analysis (Figure 1) (16,17,(20)(21)(22)(23)(24)(25). Among the 8 RCTs, seven studies were considered to be high-quality [six had scores of 5 points (17,(21)(22)(23)(24)(25) and one had a score of 4 points (20) on the Jadad scale], and one study ( 16) was considered to be mediumquality (3 points on the Jadad scale) (Supplementary Table S3). The geographical distribution of studies was relatively wide, with four studies in Asia (17,20,21,25) and four in North America (16,(22)(23)(24).…”
Section: Search Results and Study Quality Assessmentmentioning
confidence: 99%
“…Among the 8 RCTs, seven studies were considered to be high-quality [six had scores of 5 points (17,(21)(22)(23)(24)(25) and one had a score of 4 points (20) on the Jadad scale], and one study ( 16) was considered to be mediumquality (3 points on the Jadad scale) (Supplementary Table S3). The geographical distribution of studies was relatively wide, with four studies in Asia (17,20,21,25) and four in North America (16,(22)(23)(24). More details on the included RCTs, including baseline characteristics and main outcome indicators, are shown in Table 1.…”
Section: Search Results and Study Quality Assessmentmentioning
confidence: 99%
“…65 En contraparte, existen investigaciones en las que no se reporta mejoría en el control y no se han evidenciado diferencias significativas en la función pulmonar, la fracción exhalada de óxido nítrico (FeNO), la reducción en las visitas a los servicios de urgencias e ingresos hospitalarios. 46,49,66,67,68,69,70 El estudio VDKA (Vitamina D para Prevenir Exacerbaciones Asmáticas) mostró que la suplementación con colecalciferol a una dosis de 4000 UI diarias en pacientes pediátricos, con deficiencia e insuficiencia de 25-OH-D, no modificó la presencia de crisis en relación con el grupo placebo. Otros estudios apoyan esta evidencia, asegurando que no existe un impacto en la reducción de estas en población pediátrica, pero sí en adultos.…”
Section: Suplementación De Vitamina D Y Su Impacto En Asmaunclassified